Perbandingan Metode Single Moving Average dan Metode Single Exponential Smoothing dalam Peramalan Indeks Pembangunan Manusia di Kabupaten Sumenep - Amaliyatul Hasanah; Prasanti Mia Purnama; Istianah Alifia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The Human Development Index (HDI) can be defined as a comparative measurement of life expectancy, education, and living standards. HDI can fluctuate, among other things, because it is influenced by external factors, such as the COVID-19 pandemic. One of the districts that was affected in such a way that caused the HDI to decline was Sumenep district. In relation to HDI fluctuations, the single moving average and single exponential smoothing forecasting methods were implemented in this research to predict the HDI in Sumenep district in 2024. Next, the results obtained from the two methods were compared. In HDI forecasting using the single moving average method, the forecast value was 68.81 with an MSE value of 1.87, MAPE 1.379%, MAD 0.886 and MSD 0.824. Meanwhile, forecasting using the single exponential smoothing method produces a forecasting value of 68.93 with α=1.895) and a MAPE value of 0.739%, MAD 0.464 and MSD 0.272.